Effect of obesity on early blood–brain barrier disruption following transient focal cerebral ischemia - C. Li; Z. Jiang; W. Lu; D. Arrick; K. McCarter; H. Sun (Obesity Science & Practice, 2016)
Summary Objective We determined the effect of obesity on early post‐ischemic blood–brain barrier (BBB) disruption. Methods Male C57BL/6J mice were fed a high‐fat diet (HFD) or standard chow for 16 weeks. Transient focal cerebral ischemia was induced by directly ligating the middle cerebral artery for 2 h. Early BBB disruption was assessed by measuring Evans Blue and sodium fluorescein extravasation at 3 h of reperfusion. Results Obesity produced an increase in cerebral vasodilation/hyperaemia during reperfusion. N(omega)‐propyl‐L‐arginine and 7‐nitroindazole (neuronal nitric oxide synthase inhibitors) failed to alter the cerebral vasodilation/hyperaemia in lean mice, but significantly inhibited the cerebral vasodilation/hyperaemia in obese mice. The magnitude of early post‐ischemic BBB disruption was significantly greater in obese mice compared with lean mice. Topical treatment with N(omega)‐propyl‐L‐arginine, 7‐nitroindazole or N(omega)‐propyl‐L‐arginine, 7‐nitroindazole (a non‐specific nitric oxide synthase [NOS] inhibitor) completely abolished the BBB disruption in lean mice, but only partially suppressed the BBB disruption in obese mice. Furthermore, a reduced matrix metallopeptidase (MMP)‐9 activity and increased endothelial NOS accompanied with unchanged protein expression of tight/adherens junctions were found in cerebral cortex of obese mice. Conclusions Our findings suggest that obesity exacerbates early post‐ischemic BBB disruption via a mechanism independent of MMP or NOS. HFD exacerbates BBB disruption at 24 h of reperfusion via MMP‐9.